2020
DOI: 10.36560/13920201069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rainfall variability on the production of Vigna unguiculata (L.) Walp. in the semi-arid region of Paraíba

Abstract: Agricultural production in semi-arid areas of the globe is dependent on species adapted to conditions of low availability of resources, such as water. Cowpea (Vigna unguiculata L. Walp.) is a vegetable widely grown in regions with water restrictions, however, even with its good adaptability, it is vulnerable to the effects of prolonged droughts. In this sense, this research aimed to analyze the influence of rainfall patterns on the production dynamics of cowpea during the period of fifteen years (2002-2016) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In Brazil, the cultivation of this fabaceae occurs predominantly in the North and Northeast regions on small and medium-sized rural properties and under rainfed conditions ( Guimarães et al., 2020 ). Thus, despite its rusticity, some research has demonstrated that cowpea productivity in these regions is strongly affected by water deficits in at least one of its phenological phases ( Silva et al., 2020 ; Souza et al., 2020a ). According to data published by CONAB (2023) , although the northeast region has the largest area cultivated with this species, its productivity (411 kg ha -1 ) is lower than the central-south region (1,024 kg ha -1 ), which presents greater technological innovations.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the cultivation of this fabaceae occurs predominantly in the North and Northeast regions on small and medium-sized rural properties and under rainfed conditions ( Guimarães et al., 2020 ). Thus, despite its rusticity, some research has demonstrated that cowpea productivity in these regions is strongly affected by water deficits in at least one of its phenological phases ( Silva et al., 2020 ; Souza et al., 2020a ). According to data published by CONAB (2023) , although the northeast region has the largest area cultivated with this species, its productivity (411 kg ha -1 ) is lower than the central-south region (1,024 kg ha -1 ), which presents greater technological innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Research aimed at improving plant species resistance to abiotic factors has been gaining more and more notoriety in the world. Among the plants with a tolerance to salinity, cowpea (Vigna unguiculata (L.) Walp) is an example, a species well adapted to the edaphoclimatic conditions of the northeast region of Brazil (Ayers & Westcot, 1999;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do seu cultivo e rusticidade, algumas pesquisas têm demonstrado que a produtividade do feijão-caupi pode ser afetada de forma drástica pela deficiência hídrica em pelo menos uma das fases de seu desenvolvimento, podendo apresentar baixas produtividades quando é submetido às práticas inadequadas de manejo (SOUZA et al, 2020;SILVA et al, 2020). O déficit hídrico é um fator agravante para a perda da produtividade vegetal, por afetar o desenvolvimento e limitar a assimilação líquida de carbono (CAVALCANTE, 2021).…”
Section: Introductionunclassified